EFFECT OF WESTWARD MOVING CLOUD ORGANISATIONS IN WEST AND NEAR EQUATORIAL PACIFIC OCEAN ON THE MONSOON RAINFALL OF INDIA - LAL , ASOI; SUNDAR , R. S. (MAUSAM, 1994)
Th en: are various synoptic s)’)leDls which affect the rainfall over India during southwest mansoon season directly or indirectly. AJ’110 J12 them. one subject of interest is the westward movina cloud pulses over th e equatorial wt’sl Pacific region. An attempt h as been made to connect the satellite c10uJ pulses in the eq ua torial west Pacific. ns seen in the INSAT· I geostationary satellite imageries. with the rai nfall of selected meteorological subqh ·i on o f Ind ia v.tlkh an: seemingly affected by Ih ’ pulses.